0.16(24)+0.04x=0.08(18+x)

Simple and best practice solution for 0.16(24)+0.04x=0.08(18+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.16(24)+0.04x=0.08(18+x) equation:


Simplifying
0.16(24) + 0.04x = 0.08(18 + x)

Multiply 0.16 * 24
3.84 + 0.04x = 0.08(18 + x)
3.84 + 0.04x = (18 * 0.08 + x * 0.08)
3.84 + 0.04x = (1.44 + 0.08x)

Solving
3.84 + 0.04x = 1.44 + 0.08x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.08x' to each side of the equation.
3.84 + 0.04x + -0.08x = 1.44 + 0.08x + -0.08x

Combine like terms: 0.04x + -0.08x = -0.04x
3.84 + -0.04x = 1.44 + 0.08x + -0.08x

Combine like terms: 0.08x + -0.08x = 0.00
3.84 + -0.04x = 1.44 + 0.00
3.84 + -0.04x = 1.44

Add '-3.84' to each side of the equation.
3.84 + -3.84 + -0.04x = 1.44 + -3.84

Combine like terms: 3.84 + -3.84 = 0.00
0.00 + -0.04x = 1.44 + -3.84
-0.04x = 1.44 + -3.84

Combine like terms: 1.44 + -3.84 = -2.4
-0.04x = -2.4

Divide each side by '-0.04'.
x = 60

Simplifying
x = 60

See similar equations:

| -(6x+3)-(8x-7)=8-(5x+1) | | 6m-8=2+9m-6 | | 10-4x=-2+8x | | 2x+13=37 | | 3t=1 | | 4y-12=-3y | | [x]-y=2 | | 3t=-1 | | 4x+43x+30x=0 | | 2y=1-xy | | 1-0x=0 | | .14y+6=-19 | | 3x-2x=6 | | 15+k=-9 | | b+2b+(b+15)=95 | | 6=13+q | | 11z=-33 | | 6(-4)= | | 8*-7= | | (x^2)=-4 | | y+23=-1 | | -29+q=4 | | (2x+6)*(x+5)=a | | d-4=-25 | | 5(2x-3)+7=10x-8 | | (x+100)+(x)+(x-50)=500 | | -7=7+n | | (x+12)2=196 | | q-24=-20 | | r(x)=x^2+4x-32x-8 | | (x^2)+5x+4=0 | | r-16=14 |

Equations solver categories